Computational materials design of a corrosion resistant high entropy alloy for harsh environments. (August 2018) - Lu, Pin; Saal, James E.; Olson, Greg B.; Li, Tianshu; Swanson, Orion J.; Frankel, G.S.; Gerard, Angela Y.; Quiambao, Kathleen F.; Scully, John R.
Abstract: The integrated computational materials engineering approach is inherently well suited to explore the vast, multi-dimensional high entropy alloy (HEA) compositional and processing space, and has been adopted in this work, coupled with empiricism, to the design of highly corrosion resistant HEAs. Using the combination of empirical and computational approaches, three non-equimolar HEA compositions were identified for their predicted ability to form a single-phase structure and to exhibit high corrosion resistance. One of them, Ni38 Cr21 Fe20 Ru13 Mo6 W2, was successfully synthesized on the lab-scale and homogenized at 1250 °C for 120 h. Exceedingly high corrosion resistance of the Ni-rich HEA was demonstrated in electrochemical testing. Graphical abstract: Unlabelled Image